Evaluating impact of digitalization on higher education quality - Nguyen, Phong Thanh; Nguyen, Quyen Le Hoang Thuy To; Huynh, Vy Dang Bich (Intelektual Pustaka Media Utama, 2025)
This research employs the spherical fuzzy analytic hierarchy process (SFAHP) to prioritize key factors shaping the higher education quality in Ho Chi Minh City, Vietnam within the context of increasing digitalization. Through a structured hierarchy encompassing criteria such as accessibility of digital resources, adaptability and innovation, pedagogical integration, student engagement, and technological infrastructure, a novel decision-making approach was applied in this study to evaluate the relative importance of these facets, using in-depth expert interviews. The findings underscore pedagogical integration and student engagement as pivotal, indicating the essential role of innovative teaching methodologies integrated with technology. Additionally, accessibility of digital resources emerges as critical, emphasizing the imperative of equitable access to technological tools for diverse student demographics. Lower-ranked criteria such as adaptability and innovation and technological infrastructure, though deemed less critical, are foundational for fostering an agile, innovative, and technology-empowered educational ecosystem. The implications drawn from these findings provide a strategic direction for policymakers and educational stakeholders, aiming to enhance the quality, accessibility, and relevance of higher education in Vietnam’s dynamic digital landscape. This framework could be expanded to different educational contexts to effectively integrate technology in learning environments.